The Efficacy of Periodic Complete Blood Count Tests in Evaluation of the Health Status of Radiation Workers in Iran: A Systematic Review - Asma ZARE; Seyed Mohammad Javad MORTAZAVI (Tehran University of Medical Sciences, 2020)
Background: Periodic medical examinations of radiation workers are routinely conducted in many countries. Although low dose radiation (LDR) is not expected to cause a significant effect on blood count, the periodic examination usually includes reviewing the work history, general medical history, a physical examination and collecting a blood sample. Despite lymphocytes are the most sensitive cells to radiation, their counts do not show any significant change as long as the radiation level is less than a few hundreds of millisievert (mSv). In spite of this, in Iran, radiation workers, even those who work in diagnostic radiology departments, are regularly examined for blood count changes. Methods: After a detailed search in PubMed, ISI, Scopus, SID and Google Scholar, only 12 out of 650 articles matched our criteria. A review of these 12 reports was conducted. The full texts were fully reviewed by the authors. Results: The complete blood count (CBC) test has a very low efficacy in evaluation of the adverse health effects of ionizing radiation in radiation workers. Therefore, finding alternative methods with a higher efficacy is recommended. Conclusion: CBC tests cannot be introduced as valid markers of potential radiation effects in most occupational exposures. Given this consideration, in periodic tests of radiation workers, cytogenetic tests can be the gold-standard method. In particular, due to its relatively low cost and good sensitivity and specificity, the dicentric assay can be promising. Moreover, the simple and rapid evaluation of micronuclei by fast automated scoring systems can be a good alternative for current low efficacy CBC tests.